PERILAKU POLITIK MASYARAKAT DALAM PEMILIHAN KEPALA DESA (Studi Pada Masyarakat Desa Kutasari Kecamatan Cipari Kabupaten Cilacap) - Amirotun Sholikhah (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2014)
This study was aimed at revealing society’s political behavior on the election of head village in Kutasari, District of Cipari, Cilacap Regency. This study used descriptive qualitative approach and data were collected through observation, in depth interviews, and documentation. It is found that in the election of head village in 2013, most of the voters had affective orientation and only few of them had cognitive orientation – i.e. voters elected their candidate on the bases of like and dislike feeling, not on the bases of candidate’s capability. It is also revealed that this behavior was influenced by direct social political environment, namely family, religion, education, and group relation.